Edukasi Pemilihan Alat Kontrasepsi Pada Wanita Usia Subur, Pasangan Usia Subur Dan Ibu Nifas - Liliek Pratiwi; Hutari Puji Astuti; Harnanik Nawangsari; Raudya Setya Wismoko Putri (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
The family planning program is the main pillar in preventing risky pregnancies and reducing maternal mortality and infant mortality. the prevalence of contraceptive use by married women is projected to be 62.2%. The percentage continues to increase until it reaches 64.4% in 2030. The level of achievement in the use of contraceptives can be seen from the coverage of couples of childbearing age and postpartum mothers. The number of mothers giving birth in 2021 will be 25,430 who will become new family planning participants. The importance of educating the public is to increase understanding regarding the selection of appropriate contraceptives for couples of childbearing age and postpartum mothers. The aim of this education is to increase knowledge regarding the selection of appropriate contraceptives, especially for couples of childbearing age and postpartum mothers. This education uses community service methods with outreach to women and couples of childbearing age and also post partum mothers, using power points and pamphlets. The results of this education showed an increase in public knowledge during the pretest and posttest.